Experimental study on dynamic characteristics of a monopile foundation based on local scour in combined waves and current. (15th December 2022) - Zhang, Bin; Li, Junhan; Liu, Wei; Zhang, Huaiyuan; Shi, Pengkun; Fu, Xiaoli
Abstract: Scour is one of the key factors causing the collapse of buildings (structures) in water. Pile foundations are often subject to the combined actions of waves and current, resulting in weakened soil overturning resistance and changes in natural vibration frequency, which may lead to vortex-induced vibration under the action of fluid flow and cause fatigue damage. A series of experiments under current-only, wave-only, and combined wave-current conditions were carried out in a wave-current flume to investigate the scour phenomenon around a monopile and the change in natural vibration frequency of the monopile foundation along the flow and vertical directions caused by local scour. The scour depth under combined wave-current conditions is greater than that under current-only conditions, and increases accordingly with the increase of the flow velocity and the decrease of the water depth. Furthermore, the scour phenomenon under different flow patterns was analyzed according to the variation of pulsation pressure. The empirical formula for the natural vibration frequency of the monopile foundation considering the local scour under current-only and combined wave-current conditions was established respectively. Compared with the experimental results, the maximum error is 10%, indicating that the empirical formula has a high degree of confidence. The above empirical formula obtained from the indoor scale model is applied to the field test, and the maximum relative error is 14.37%, which indicates that the empirical formula is also suitable for the prototype scale. Highlights: The local scour around the monopile foundation changes in different patterns under different flow conditions. The dynamic pressure distribution under current-only and wave-only is butterfly-shaped and fishtail-shaped respectively. The relationship between the natural vibration frequency of the pile foundation and the scour depth is nonlinear. Establish empirical formulae for the natural vibration frequency of the pile foundation under local scour .